PROJECT BASED LEARNING PEMBELAJARAN IPA MATERI MINUMAN SEHAT DI SCIENCE TECHNO PARK UNITRI PADA SISWA KELAS 5 SDN 1 LANDUNGSARI KABUPATEN MALANG - Anwar, Moh. Farid Nurul; Mitasari, Zuni; Rhozhana, Kardiana Metha; Istikomayanti, Yuswa; Khumaidah, Amalia (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2024)
Learning Media are learning facilities and infrastructure that must be present in education. SDN 1 Landungsari has various learning media to support classroom learning. It's just that there are several media that don't yet exist, such as microscopes, slides, dropper pipettes and glass beakers for testing healthy food/drinks in class 5 science lesson content, theme 3, sub-theme 2. For this reason, based on the problems above, PKM Project Based Learning is carried out in Science Learning. Material for Healthy Drinks at Science Techno Park Unitri for Grade 5 Students at SDN 1 Landungsari, Malang Regency, this is a solution to problems. Efforts to implement the solutions that have been offered are carried out through preparation, implementation and evaluation activities. The activity was held on August 30 2022 by bringing 5th grade students of SDN 1 Landungsari along with 5th grade teachers to the UNITRI science Techno park. This activity succeeded in concretizing students about the theory of bacteria, this can be seen from the students' drawings and several students' questions that linked the bacteria they saw on YouTube with direct observations through a microscope.